(3GdeMGSHI GdYGeI (B1 (3h (B2 : s (3eWHhYI ehLgI dWdHI GdSfI GdChdi LPY eTJQc d e O (BLMD / s - (3HhSdjeGfj, UdjMIs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2022)
(3GdGWGQ GdfXQj ddeMGSHI GdeGdjI h BdjGJ h bhGYO eSc GdeMGSHI GdeGdjI , SjQ MSGHGJ GdejRGfjI h GdeYGdLI GdeMGSHjI , SjQ MSGHGJ GdfJGFL h GdeYGdLI GdeMGSHjI h CYeGd fgGjI GdSfI h bjhO GdJShjI , YQV h JbOje GdbhGFe GdeGdjI GdNJGejI (B.s
(3eQGLY U(B.141s
Keywords: (3GdeMGSHI GdeGdjIs